(untitled) (UNED Research Journal, 2019)
Introduction: One of the most commonly used methods of waste management is landfilling, which has been a major environmental concern. Objective: To examine the effect of leachate on Clarias gariepinus. Methods: We tested Clarias gariepinus (n=700) with varying concentrations of leachate (0, 10, 15, 20 and 25%) from the Amoyo dumpsite, Ilorin, Nigeria. After 28-day exposure, haematological, biochemical, bacteriological and histopathological assays were carried out. Results: pH ranged from 7,78 to 13,97; cadmium, iron, lead, manganese and zinc were 178-, 134-, 6248-, 400- and 3-fold, respectively, higher than the regulatory limits for waterbodies, while copper fell within the limits. Values of red blood cell, haemoglobin, packed cell volume, mean cell volume, mean cell haemoglobin, mean cell haemoglobin concentration, lymphocytes and monocytes were significantly lower than the control. Conversely, white blood cell, neutrophils and eosinophils increased in a concentration-dependent manner. There were tissue-specific differences in the responses of all biochemical parameters investigated except for protein that significantly decreased in all the tissues. veitisiete bacterial isolates classified into seven genera including Bacillus, Klebsiella, Pseudomonas, Staphylococcus, Acinetobacter, Escherichia and Micrococcus were recorded from the leachate and selected organs of C. gariepinus. The total bacterial, viable coliform and total counts in the leachate were 4,2×106CFU/mL, 3,8×108CFU/mL, 3,6× 106CFU/mL and 2,7×108CFU/mL, respectively. The highest counts were recorded in the gills (14,2×106CFU/mL) and lowest in the muscle (2,7×106CFU/mL) at the highest and least concentration of the leachate, respectively. Most of the bacteria isolated from the leachate were also recovered from the fish organs. Escherichia coli had the highest frequency of occurrence (26%). Conclusion: This study revealed that toxic constituents of the leachate elicited deleterious changes in the bacteriology and physiology of C. gariepinus.